The Early Record of a Modern Administrative Dilemma - Scott, William G. (Academy of Management Journal, 1959)
Traces in broad terms from 1900 to 1940 the development of three points of view on one major social issue, the dilemma of individualism. Influences of the individualistic ethic and the social ethic ideologies on management theory; Characteristics of scientific management; Discussion on the dilemma from the point of view of non-fiction social criticism.